New insights into the production of fucoxanthin by mixotrophic cultivation of Ochromonas and Microcystis aeruginosa. (November 2022) - Gao, Lei; Wang, Fengjing; Wu, Tianyue; Zhou, Qi; Zhang, Duo; Hou, Xinbin; Zhang, Xinpeng; Ye, Jingrun; Ma, Yan; Wang, Zhipeng; Song, Lirong; Chen, Wei
Graphical abstract: Highlights: A golden algal strain capable of engulfing M. aeruginosa and accumulating Fx was isolated and identified as Ochromonas sp. strain-01. An innovative and efficient way to produce Fx was established for the first time by using M. aeruginosa as baits in mixotrophic cultivation with Ochromonas . Engulfing M. aeruginosa greatly promoted the growth and Fx accumulation in Ochromonas sp. strain-01 due to the sufficient nutrients supply by M. aeruginosa . Abstract: Fucoxanthin (Fx) has attracted great interest due to its remarkable biological activities such as antioxidant and anti-obesity, and its increasing demands in biopharmaceutical and cosmetic fields. However, its commercial production is limited by low yield and high cost. In this study, we isolated and identified a species of golden algae ( Ochromonas sp.) capable of engulfing Microcystis aeruginosa ( M. aeruginosa ) and accumulating Fx. After 72 h mixotrophic cultivation of Ochromonas sp. and M. aeruginosa, the algal culture changed from green to yellow–brown, and the content of Fx and the daily production rate were up to 11.58 mg g −1, and 1.315 mg L -1 d -1, respectively. The utilization rate of M. aeruginosa was 527.27 fg cell −1 . This study will not only provide a new thought to produce Fx in an efficient, low-cost, and sustainable way but an innovative method for the control and treatment of harmful cyanobacterial blooms from eutrophic freshwaters as well.